Desafios e perspectivas dos educandos e de seus familiares no processo de mudança da escola do campo para a escola da cidade em Abaetetuba-PA - GONÇALVES, Valdicéia dos Santos (2019)
Most rural schools in the municipality of Abaetetuba, especially rural roads and extensions only offer schooling only for the initial grades of elementary school. Thus students in the field need to migrate to the city to continue their studies. Thus, the objective of this work was: to analyze the challenges and perspectives of families and students regarding the departure from the School and the inclusion in a new socio-educational reality. The methodological processes were constituted beyond the theoretical references in a qualitative research. Semi-structured interviews were conducted with forty people (25 students, 10 parents and 5 employees) in five schools in four rural communities in the municipality of Abaetetuba, Pará, Brazil. It was observed that students face many difficulties to continue their studies, such as: transportation, extensions, financial, disciplines, content, lack or minimal allocation of resources and difficulties in the physical structures of schools, among others. The research points out that if there were possibilities students and their families would prefer that community schools offer all grades. Thus, it is necessary to have greater attention from governments regarding the provision of schooling, and education focused on the reality of the countryside.